A 422-Year Reconstruction of the Kaiken River Streamflow, Xinjiang, Northwest China - Heli Zhang; Huaming Shang; Feng Chen; Youping Chen; Shulong Yu; Tongwen Zhang (Atmosphere, 2020)
Our understanding of Central Asian historical streamflow variability is still limited because of short instrumental hydrologcial records. Based on tree-ring cores collected from three sampling sites in Kaiken River basin near Tien Shan, a regional tree-ring width chronology were developed. The correlation analysis showed that the runoff of Kaiken River from previous August to current June was significantly correlated with the regional chronology, and the high correlation coefficient was 0.661 (P < 0.01). Based on the regional chronology, the August-June runoff of Kaiken River has been reconstructed over the past 422 year, and it accounted for 43.7% of actual runoff variance during the common period 1983–2013. The reconstruction model is reliable, and the trend of observed and reconstructed data is relatively consistent. The results of multi-taper spectral analysis for the runoff reconstruction indicated some remarkable cycles for the past 422 years; the 11.5-year cycles correspond to the solar cycle and is found widely in runoff reconstructions in Central Asia. This may imply a solar influence on the hydroclimate variations of Tien Shan. The runoff reconstruction of Kaiken River compares well with runoff reconstructions the Urumqi River and Manas River, and implies that there is a common driving factor for the runoff in central Tien Shan, China. The analysis of linkages between climate variation and the runoff reconstruction of Kaiken River shows that there is a relationship between extremes in runoff variation and abnormal atmospheric circulations. Our 422-year steamflow reconstruction provides long-term perspective on current and 20th century hydrological events in central Tien Shan, is useful for aids sustainable water management and addresses regional climate change challenges.